Determination of nine nucleosides in Rhizoma Paridis by quantitative analysis of multi‐components via a single marker method. Issue 9 (16th March 2021) - Xie, Jing; Wang, Run‐Yue; Yong, Li; Gong, Yi‐xin‐yue; Ding, Li‐Sheng; Xin, Ying; Wang, Hong‐Li; Xue, Ying; Qing, Lin‐Sen
Abstract: In this work, a new quantitative analysis method of multi‐components analysis via a single marker strategy coupled with high‐performance liquid chromatography (HPLC) analysis, was proposed to analyze nine nucleosides (cytidine, uridine, 2′‐deoxyuridine, inosine, guanosine, 2′‐deoxyguanosine, thymidine, adenosine, and 2′‐deoxyadenosine) as quality control markers in Rhizoma Paridis. Guanosine was set as the internal reference substance, whose content in Rhizoma Paridis was determined using conventional external standard method. Then, relative correction factors between guanosine and the other eight nucleosides were measured respectively. The amounts of the other eight components were calculated according to the relative correction factors by the quantitative analysis of multi‐components via a single marker method. Finally, the result of vector angle cosine analysis showed that there was no significant difference of the contents between the external standard method and the quantitative analysis of multi‐components via a single marker method, indicating that the quantitative analysis of multi‐components via a single marker method can be applied for the quality control of Rhizoma Paridis. As far as we know, this is also the first report to analyze nucleosides by the quantitative analysis of multi‐components via a single marker method, providing an efficient and promising quality assessment method for other traditional Chinese medicine containing nucleosides.